PREPARATION OF CELLULOSE WHISKERS MONOLAYERS ON WAFER SILICON SURFACE BY LANGMUIR–BLODGETT TECHNIQUE (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
A detailed description of the preparation of cellulose whiskers monolayer on the silicon wafer surface by Langmuir–Blodgett technique is presented. The Langmuir–Blodgett transfer is realized both by continued compression and sinusoidal compression-expansion conditions of dioctadecyldimethyl ammonium bromide–cellulsoe nanocristals bilayer. The AFM analyze of the cellulose nanocrystals monolayer has shown, that the cellulose whiskers monolayer is more compacted, when the transfer is realized in sinusoidal compression-expansion condition.
Keywords: cellulose nanocrystals, plant cell wall, Langmuir–Blodgett transfer, Atomic Force Microscopy (AFM), surface pressure